Calcium influx rescues adenylate cyclase-hemolysin from rapid cell membrane removal and enables phagocyte permeabilization by toxin pores. - Radovan Fiser (Public Library of Science (PLoS), 2012)
Bordetella adenylate cyclase toxin-hemolysin (CyaA) penetrates the cytoplasmic membrane of phagocytes and employs two distinct conformers to exert its multiple activities. One conformer forms cation-selective pores that permeabilize phagocyte membrane for efflux of cytosolic potassium. The other conformer conducts extracellular calcium ions across cytoplasmic membrane of cells, relocates into lipid rafts, translocates the adenylate cyclase enzyme (AC) domain into cells and converts cytosolic ATP to cAMP. We show that the calcium-conducting activity of CyaA controls the path and kinetics of endocytic removal of toxin pores from phagocyte membrane. The enzymatically inactive but calcium-conducting CyaA-AC⁻ toxoid was endocytosed via a clathrin-dependent pathway. In contrast, a doubly mutated (E570K+E581P) toxoid, unable to conduct Ca²⁺ into cells, was rapidly internalized by membrane macropinocytosis, unless rescued by Ca²⁺ influx promoted in trans by ionomycin or intact toxoid. Moreover, a fully pore-forming CyaA-ΔAC hemolysin failed to permeabilize phagocytes, unless endocytic removal of its pores from cell membrane was decelerated through Ca²⁺ influx promoted by molecules locked in a Ca²⁺-conducting conformation by the 3D1 antibody. Inhibition of endocytosis also enabled the native B. pertussis-produced CyaA to induce lysis of J774A.1 macrophages at concentrations starting from 100 ng/ml. Hence, by mediating calcium influx into cells, the translocating conformer of CyaA controls the removal of bystander toxin pores from phagocyte membrane. This triggers a positive feedback loop of exacerbated cell permeabilization, where the efflux of cellular potassium yields further decreased toxin pore removal from cell membrane and this further enhances cell permeabilization and potassium efflux.